Education and the Liberalism Perspective - Syaharani, Annisa Riza (Journal of Innovation in Teaching and Instructional Media, 2023)
The birth of liberalism is inseparable from recent developments in the West since the Renaissance and the Enlightenment. This development underlies many significant changes in Western culture and civilization, positioning the world of education strategically on the global stage. The influence extends across all nations, necessitating the need to adapt to the requirements of liberalization. In fact, liberalism, which supports the progress of the West through the development of science, technology, and industrialization, has left suffering and crises for humanity. This has triggered strong reactions and led to the emergence of socialism and communism. This article seeks to investigate the extent to which liberalism influences education. Additionally, the article aims to explore various positive and negative impacts. Therefore, we hope this article can foster a critical attitude towards this issue.